Addressing Pronunciation Challenges Among Filipino Senior High School Learners: Strategies and Pedagogical Implications - El Chamberlain Abellana (Scientia Publica Media, 2025)
This study investigates common pronunciation challenges faced by Filipino Senior High School learners in their English language acquisition. It explores factors contributing to these difficulties, such as L1 influence, dialectal variations, and the lack of phonetic awareness. Additionally, it examines pedagogical strategies to enhance pronunciation skills and improve learners’ intelligibility. A total of 60 students from different strands are selected to participate in pronunciation tests and surveys. Through a mixed-methods approach involving pronunciation tests, surveys, and teacher interviews, the study identifies key error patterns, including difficulties with consonant sounds (/f/ vs. /p/, /v/ vs. /b/), vowel shifts, and incorrect word stress placement. These challenges are attributed to linguistic interference, limited exposure to native pronunciation models, and ineffective pronunciation instruction in the classroom. Findings suggest that explicit phonetic instruction, communicative activities, and technology-assisted learning can significantly improve learners’ pronunciation proficiency. The use of audiovisual materials, phonetic transcription, and real-life conversation practice is found to be effective in addressing these challenges. Furthermore, teacher training in pronunciation instruction and the integration of pronunciation-focused activities in English curricula are recommended to enhance students’ speaking skills. By addressing these pronunciation barriers, students can develop greater confidence in spoken English, facilitating better academic and professional communication.